Psychological Control helps to counter sports anxiety: A moderating role of coach relationship - Dr. Muhammad Awais Bhatti; Dr. Abbas N Albarq (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Without access to skilled coaches, sports anxiety is frequent among athletes. In Saudi Arabia, the lack of emotional intelligence and other mental problems prevent athletes from doing better with sports anxiety. This study examines the direct influence of psychological Control, coach-athlete interaction, and coach support on sports anxiety in Saudi Arabia. This study also analyzes the moderating effect of coach relationship and support on the relationship between psychological Control and athletic performance. A Likert scale questionnaire is utilized to collect cross-sectional data from Saudi Arabian college athletes. When players have a good relationship with their coach, they can have greater psychological Control over their athletic performance, as revealed by the study. This research is founded on a novel concept, and its theoretical framework contributes to our understanding of sports anxiety. In addition, the research produced exceptional practical and theoretical consequences that are crucial for combating sports anxiety practically and advancing our understanding of sports anxiety, respectively. The research findings suggest future directions based on the literature that provide researchers with new insight into investigating deeper links within the sports anxiety model.